Komunikasi Internal Pt. Solid Logistics Memengaruhi Meningkatnya Employee Engagement - Sukatno Tekad Sukatno; Martani Huseini; Imam Syafganti; Irwansyah Irwansyah (Inter Komunika, 2018)
Abstract. The concerns of this reaseacrh to determine and analyze the impact of internal communication towards Employee Engagement at PT. Solid Logistics. The Internal Communication Theory used in this study refers to the opinion of Lawrence D. Brennan (1960) while for Employee Engagement based on the views of William H. Macey (2009). It is explanatory research. The population in this research were all employees of PT. Solid Logistics. The data is collected through the distribution of questionnaires, observation, interviews, documentation, literature studies, and data of the company. Data analysis techniques are used quantitatively and narrated according to the results of the research. The results of the reasearch is indicating that internal communication has a significant impact on the Employee Engagement at PT. Solid Logistics.Keywords: Organizational Communication, Internal Communication, Employee EngagementAbstrak. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh komunikasi internal terhadap Employee Engagement di PT. Solid Logistics. Teori Komunikasi Internal yang digunakan dalam penelitian ini  mengacu  pada  pendapat  Lawrence. Brennan (1960) sedangkan untuk Employee Engagement berdasarkan pandangan dari William H. Macey (2009). Jenis penelitian ini adalah eksplanatif. Populasi dalam penelitian ini adalah seluruh karyawan PT. Solid Logistics. Teknik pengumpulan data dilakukan melalui penyebaran kuesioner, observasi, wawancara, dokumentasi, studi kepustakaan, dan data-data perusahaan. Teknik analisis data yang digunakan secara kuantitatif dan dinarasikan sesuai dengan hasil penelitian. Hasil dari penelitian menunjukkan bahwa komunikasi internal memiliki pengaruh yang cukup signifikan terhadap Employee Engagement di PT. Solid Logistics.Kata kunci: Komunikasi Organisasi, Komunikasi Internal, Employee Engagement